Boje, eidam, polder: Contribution to the description of Dutch loanwords in Czech - Krizova, Katerina (Bohemica Olomucensia, 2018)
This article focuses on Dutch loanwords in the Czech language which were so far not dealt with intensively in the Czech literature. Our aim is to provide a brief characteristic of more than 100 words listed in the Dutch database Uitleenwoordenbank (Van der Sijs 2015) in the category Dutch loanwords in Czech. In the description we concentrate on the way, the process of borrowing is realized in the Czech language, as well as on the adaptation of these words to the Czech language system. We describe also the thematic fields where these words are mostly to be found. Moreover, we analyse their usage in the contemporary Czech based on the representative corpus of contemporary written Czech SYN2015.As Dutch and Czech have never been in direct and intensive language contact, the majority of analysed Dutch loanwords in Czech were borrowed via another languages - primarily German, to a lesser extent English or eventually French or Russian.
Keywords: borrowing; Czech; Dutch; loanword; language contact; etymology